THE EFFECT OF DISCOVERY LEARNING MODEL ON STUDENTS’ SCIENTIFIC ATTITUDES AND PERSEVERANCE IN SOLVING GRAPH PROBLEMS - Ismi Widyaningrum (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to determine the effect of Discovery Learning model on students’ scientific attitudes and perseverance in solving graph problems in the Discrete Mathematics course. The research employed a quantitative approach with a quasi-experimental design involving students of Mathematics Education Study Program at STKIP SyekhManshur. Data were collected through questionnaires, observations, and tests, and analyzed using descriptive statistics and paired t-tests. The results showed a significant improvement in students’ scientific attitudes, with the average score increasing from 69.21 to 83.57, and in perseverance, from 66.43 to 81.79. Test scores also increased from 62.14 to 82.57, with the t-test indicating a significant difference (tcount = 6.21 >ttable = 2.16). These findings indicate that the implementation of Discovery Learning can enhance students’ scientific attitudes, perseverance, and their ability to understand and solve graph problems independently and scientifically.